2017
DOI: 10.1007/s13280-017-0945-3
|View full text |Cite
|
Sign up to set email alerts
|

The perception of aquaculture on the Swedish West Coast

Abstract: Efforts are on the way on the Swedish West Coast to develop the capacity for cultivation of marine resources, notably of kelps. Given that this is a region of great natural and national heritage, public opposition to marine developments has been identified as a possible risk factor. This survey thus sought to shed light on awareness levels, perceptions of different types of aquaculture and on reactions to a scenario depicting future aquaculture developments on the West Coast. When asked about their general opi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…A recent study among residents along the Swedish west coast indicates e.g. that two out of five respondents are not concerned that cultivation sites will have an impact on leisure boating 26 . In addition, increasing activity along the coast could also bring cultural values and food tourism.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study among residents along the Swedish west coast indicates e.g. that two out of five respondents are not concerned that cultivation sites will have an impact on leisure boating 26 . In addition, increasing activity along the coast could also bring cultural values and food tourism.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, respondents were favourable to the scenarios depicting future aquaculture developments on the Swedish West Coast. Finally, it was found that the high-awareness group tended to be more supportive than the low or medium-awareness groups, hinting at the benefits of increasing awareness to reduce risks of public aversion and to support a sustainable development of aquaculture on the Swedish West Coast (Thomas et al 2017 ).…”
Section: Stakeholder Participation In the Seafarm Projectmentioning
confidence: 99%
“…Values and perceptions can change when knowledge emerges or initiatives come closer to (large scale) implementation. Further, the general lack of awareness about aquaculture amongst residents of the west coast, as identified in the survey, can be seen as a possible threat given that a lack of awareness could lead to conflicts and aversion to future developments (Thomas et al 2017 ). Thus, an initiative might evolve from a moderately structured to an unstructured problem.…”
Section: Reflectionsmentioning
confidence: 99%
“…; FAO ; Thomas et al . ) which, along with competition from other prospective users for marine space, impacts consumption, marketing and profitability. This is particularly true for the countries where aquaculture is a consolidated activity.…”
Section: Introductionmentioning
confidence: 99%
“…Poor perceptions of aquaculture by the general public exacerbate the challenges of improving space for aquaculture. Whereas population growth stimulates the need for high-quality food and improved food availability (Charles et al 2010), a population's social acceptance or non-acceptance of aquaculture affects the development of the sector (Bacher et al 2014;FAO 2016;Thomas et al 2017) which, along with competition from other prospective users for marine space, impacts consumption, marketing and profitability. This is particularly true for the countries where aquaculture is a consolidated activity.…”
Section: Introductionmentioning
confidence: 99%